Attenuation of hydrogen peroxide and ferric reducing/antioxidant power serum levels in colorectal cancer patients with intestinal parasitic infection - Chandramathi, S.; Suresh, K.G.; Anita, Z.B.; Kuppusamy, Umah Rani (Penerbit Universiti Sains Malaysia, 2009)
Background: This study assessed several common oxidative indices in subjects infected with intestinal parasites, as well as in colorectal cancer (CRC) patients both with and without intestinal parasites. Method: Serum levels of malondialdehyde (MDA), ferric reducing/antioxidant power (FRAP), and hydrogen peroxide (H2O2) were measured, as were plasma levels of advanced oxidation protein products (AOPP), all according to established methods. The presence of intestinal parasites was confirmed by stool examination. Results: All intestinal parasiteinfected subjects and CRC patients showed the presence of oxidative stress. Thirtysix percent of the CRC patients had intestinal parasitic infections. The levels of H2O2 and FRAP in parasite-infected subjects were significantly higher than in CRC patients, but these levels were significantly lower in the CRC patients with parasitic infections. Conclusion:Parasitic infection and CRC may contribute to oxidative stress independently, but when present together, the oxidative stress burden imposed by parasites may be attenuated.